Exercise-Induced Anaphylaxis: A Case Report and Review of the Diagnosis and Treatment of a Rare but Potentially Life-Threatening Syndrome - Nathan T. Jaqua; Matthew R. Peterson; Karla L. Davis (Case Reports in Medicine)
A 24-year-old male Marine with an uncomplicated medical history and a long history of strenuous, daily exercise presented to the emergency department after experiencing anaphylactic shock while running. Symptoms resolved following administration of intramuscular diphenhydramine, ranitidine, intravenous methylprednisolone, and intravenous fluids. On followup in the allergy clinic, a meticulous clinical history was obtained which elucidated a picture consistent with exercise-induced anaphylaxis. He had experienced diffuse pruritus and urticaria while exercising on multiple occasions over the last three years. His symptoms would usually increase as exercise continued. Prior to the first episode, he regularly exercised without symptoms. Exercise-induced anaphylaxis is a rare but potentially life-threatening syndrome that requires a careful clinical history and is a diagnosis of exclusion. Treatment is primarily exercise avoidance. Prophylactic mediations are inconsistently effective but are empirically used. Successful treatment with omalizumab was recently reported in a case of refractory exercise-induced anaphylaxis.